Antioxidant Activities and Anti-Cancer Cell Proliferation Properties of Natsuhaze (Vaccinium oldhamii Miq.), Shashanbo (V. bracteatum Thunb.) and Blueberry Cultivars - Tsuda, Hirotoshi (Plants (Basel), 2013)
Antioxidants are abundant in blueberries, and while there are many studies concerning the bioactive compound of fruit, it is only recently that the wild Vaccinium species has attracted attention for their diverse and abundant chemical components. The aim of this study was to investigate the bioactive compounds of blueberry cultivars and wild species found in Japan. Among the five extracts of the Vaccinium species, Natsuhaze (Vaccinium oldhamii Miq.) was found to be the most effective at inhibiting the growth of HL-60 human leukemia cells in vitro. Although all ethanol extracts showed a growth inhibitory effect on HL-60 cells, the degree of the effects differed among the species. The extract of Natsuhaze induced apoptotic bodies and nucleosomal DNA fragmentation in the HL-60 cells. Of the extracts tested, that of Natsuhaze contained the largest amount of total polyphenols and showed the greatest antioxidant activity, but the anthocyanin content of Natsuhaze was similar to that of rabbiteye blueberry (V. virgatum Ait.). The results showed that total polyphenols contributed to the high antioxidant activity and growth inhibitory effect on HL-60 human leukemia cells of Natsuhaze extract.